2020
DOI: 10.1177/0003489420965633
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Immobility Following Vaccination

Abstract: Objective: Vocal fold immobility (VFI) may severely affect quality of life due to dysphonia and respiratory distress. Many etiologies of this disorder have been evaluated, however the relationship between VFI and vaccination has yet to be explored. The objective of this study was to identify the relationship between VFI and vaccine administration. Methods: The Vaccine Adverse Event Reporting System (VAERS) database was queried for patients exhibiting symptoms of VFI following vaccination. Patient demographics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…Our analysis revealed the majority of cases to be unilateral (78.9%) which is consistent with Talmor et al's finding of 50% unilateral cases of vaccine related paresis [10] and with viral induced VFP, which has largely been reported as unilateral [23]. Our average time from vaccination to symptom onset was 12.1 days, which is longer than those previously described by Talmor et al in VFP patients (6.3 days) and Woo et al in extra-ocular palsies (9 days) [10,24]. However, 84.2% of our patients reported symptoms within 30 days of vaccination which is comparable to 90.0% of patients presenting with VFP [6] and 77% patients presenting with Bell's palsy [25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our analysis revealed the majority of cases to be unilateral (78.9%) which is consistent with Talmor et al's finding of 50% unilateral cases of vaccine related paresis [10] and with viral induced VFP, which has largely been reported as unilateral [23]. Our average time from vaccination to symptom onset was 12.1 days, which is longer than those previously described by Talmor et al in VFP patients (6.3 days) and Woo et al in extra-ocular palsies (9 days) [10,24]. However, 84.2% of our patients reported symptoms within 30 days of vaccination which is comparable to 90.0% of patients presenting with VFP [6] and 77% patients presenting with Bell's palsy [25].…”
Section: Discussionsupporting
confidence: 92%
“…While much of the existing literature regarding adverse reactions to vaccines describes peripheral neuropathy and other cranial neuropathies, there is a paucity of reports on vaccination induced vocal fold paresis. Talmor et al reported on twenty-two patients in the VAERS database found to have VFP following vaccination with influenza, shingles, pneumococcus, and hepatitis B vaccine 10 . Our study represents the first investigation of COVID-19 vaccination associated VFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] While most post-viral neuropathies have been linked to acute infections some have been observed after vaccination using the influenza, shingles, pneumococcus, and hepatitis B vaccines. [12] More recent reports have raised a possible temporal association between the administration of the Pfizer-BioNTech and the Oxford-AstraZeneca vaccines and the incidence of Guillain-Barre syndrome and Bell's palsy in vaccinated individuals. [13] - [16] Proposed biological mechanisms which might explain the observed association between the use of mRNA vaccines, such as the Pfizer-BioNTech vaccine, and the imbalance in the incidence of Bell's palsy in the vaccine groups compared to placebo groups, include that mRNA vaccines are associated with a marked type I interferon response which, in some individuals, may trigger and mediate a breakdown of tolerance to myelin sheath antigens leading to autoimmune neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…While most post-viral neuropathies have been linked to acute infections, some have been observed after vaccination using the influenza, shingles, pneumococcus and hepatitis B vaccines. 12 More recent reports have raised a possible temporal association between the administration of the Pfizer-BioNTech and the Oxford-AstraZeneca vaccines and the incidence of Guillain–Barré syndrome and Bell's palsy in vaccinated individuals. 13 16 …”
Section: Discussionmentioning
confidence: 99%